Weeds. Season seven [videorecording (DVD)] - Kohan, Jenji, 1969-; Parker, Mary-Louise; Parrish, Hunter, 1987-; Gould, Alexander, 1994-; Kirk, Justin; Nealon, Kevin, 1953- (Lions Gate Home Entertainment, 2012)
New York, New High! After serving three years in the joint, the onetime suburban soccer mom is making a fresh start in New York City and going back to doing what she does best: selling pot. But when some old friends return, they could send everything up in flames.